Foresight and trade-off implications for One CGIAR - CGIAR Independent Science for Development Council (CGIAR Independent Science for Development Council, 2020)
In early 2020 the CGIAR Independent Science for Development Council (ISDC) commissioned foresight reviews and a trade-off analysis report. The goal of the research was to provide ISDC members with an evidence base that would allow them to build foresight reflections and identify key challenges to consider in developing the CGIAR 2030 Research Strategy. As a first step, ISDC commissioned two expert reviews that synthesized a broad sample of existing foresight literature on the five One CGIAR impact areas. The foresight reviews were the initial phase in a stepwise approach to providing a grounding for consensus building, followed by a trade-off analysis report. This research concluded in June 2020 and was presented to CGIAR leadership.